Remote procedure call communication and control of autonomous mobile robot for indoor smart waste monitoring - Ashaari Yusof; Abdullah Man; Azmi Ibrahim; Mohamed Ashraf Husni Zai; Md. Jakir Hossen (Institute of Advanced Engineering and Science, 2026)
The integration of autonomous mobile robots (AMRs) and Internet of Things (IoT) technology has revolutionized various industries, including smart waste management (SWM). In this paper, the implementation of a customized remote procedure call (RPC) methodology was successfully demonstrated. This methodology facilitated control and monitoring of AMRs for smart indoor waste management to collect and dispose waste, monitor bin threshold levels and report relevant parameters to a cloud-based platform. Key operational parameters from the AMR and the smart bins via assembled user smart dashboard ensures seamless user monitoring for indoor waste management. Our findings underscore the relevance of RPC in advancing smart waste management technologies, contributing to operational efficiency and sustainability.